Analisis Kinerja Perdagangan Kontrak Berjangka Logam Mulia pada Periode Oktober 2009 - Desember 2009 - Mohamad Heykal; Erlin Erlin (Bina Nusantara University, 2011)
As a competitive in the industry had been caused the price of Gold commodity become fluktuative dan it make the commodity supply had not been guarantee. Based on that the investor had been tried to make commodity trading that can be used as a hedging that become effective to ensure the strategy from company management from the effect of price fluctuation that can be happen every time. The contract periode that had done in this research from the periode October, November, and December, where the fluctuation of spot and futures price can be calculated based on the correlation between spot and future price. Correlation had been used to put the hedge ratio and also the optimum contract. VaR Methode had been used to show the total risk.The average of VaR spot is Rp 12.205.950.And the VaR futures is Rp 3716803. Based On the condition of high risk and also high return, but it also depend on the investor.